Three-stage pyrolysis-catalytic dry reforming of waste polyolefins over MFI and Ni-MFI catalysts for BTEX and syngas production - Inayat, Amer; Inayat, Alexandra; Klemencova, Katerina; Schwieger, Wilhelm; Lestinsky, Pavel (Fuel, 2024)
This work presents an experimental proof-of-concept study for a three-stage pyrolysis-catalytic dry reforming process for recovering valuable chemicals from waste plastics. It is demonstrated that depending upon the catalysts, process parameters and reactor configuration, plastic waste and carbon dioxide can be converted into a diverse array of valuable chemicals which can be used as secondary feedstocks in the chemical or petrochemical industry, thus decreasing dependency on fossil resources and contributing to waste reduction. For this work, waste polypropylene was thermally pyrolyzed and the emerging vapors were passed over HZSM-5 catalyst to obtain BTEX-rich pyrolysis oil and pyrolysis gases containing mainly C1 to C4 hydrocarbons. The gaseous products were separated, mixed with CO2 and passed over Ni-silicalite-1 catalyst to obtain syngas, thus upgrading the pyrolysis gases and contributing to CO2 reduction. This study may provide new insights towards the development of processes for the chemical recycling of waste plastics and CO2.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Catalytic pyrolysis; Chemical recycling; Dry reforming; Waste management; Zeolite catalysts